2016
DOI: 10.1103/physrevx.6.041057
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium Interfacial Tension in Simple and Complex Fluids

Abstract: Interfacial tension between immiscible phases is a well-known phenomenon, which manifests itself in everyday life, from the shape of droplets and foam bubbles to the capillary rise of sap in plants or the locomotion of insects on a water surface. More than a century ago, Korteweg generalized this notion by arguing that stresses at the interface between two miscible fluids act transiently as an effective, nonequilibrium interfacial tension, before homogenization is eventually reached. In spite of its relevance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(34 citation statements)
references
References 74 publications
3
31
0
Order By: Relevance
“…They carried out experimental measurements of the Saffman-Taylor instability in a Hele-Shaw cell with miscible complex fluids including colloidal dispersions. Their measurements went beyond confirming Korteweg's theory and showed that EIT is also a function of particle structure (basically size and shape) together with particleparticle and particle-solvent interactions (Truzzolillo et al 2016). Effective interfacial tension is expected to have relevance in many fields starting from material processing to multiphase complex fluid dynamic problems involving droplet and bubbles formation, jetting, coalescence and break-up of droplets (Truzzolillo & Cipelletti 2017).…”
Section: Introductionmentioning
confidence: 92%
“…They carried out experimental measurements of the Saffman-Taylor instability in a Hele-Shaw cell with miscible complex fluids including colloidal dispersions. Their measurements went beyond confirming Korteweg's theory and showed that EIT is also a function of particle structure (basically size and shape) together with particleparticle and particle-solvent interactions (Truzzolillo et al 2016). Effective interfacial tension is expected to have relevance in many fields starting from material processing to multiphase complex fluid dynamic problems involving droplet and bubbles formation, jetting, coalescence and break-up of droplets (Truzzolillo & Cipelletti 2017).…”
Section: Introductionmentioning
confidence: 92%
“…Collectively these experiments show that the theory of Paterson captures the behavior of molecular newtonian liquids where interdiffusion rapidly smears the concentration profile, such that capillary forces can be neglected. On the other hand, we have recently shown [44] that the wavelength characterizing the onset of radial viscous fingering, does depend on the injection rate and, most importantly, on the physico-chemical nature of the two fluids in contact. These results were obtained with colloidal suspensions brought in contact with their own solvent, for which interdiffusion can be neglected on the time scale of the experiments.…”
Section: Displacing Fluids: Saffman-taylor Instabilitiesmentioning
confidence: 99%
“…A unified and solid framework allowing one to predict the onset and the evolution of viscous fingering in miscible fluids remains elusive unless transient capillary forces are invoked. The latter depend on the physicochemical nature of the fluids in contact [44] and are not negligible in the case of sharp compositional mismatches. Panel A: Viscous fingering created by water displacing a polysaccharide aqueous solution.…”
Section: Displacing Fluids: Saffman-taylor Instabilitiesmentioning
confidence: 99%
See 2 more Smart Citations